Ectomicorrização e composto de água residuária de suinocultura no crescimento de Ilex paraguariensis A. St.-Hil. cultivada em solo contaminado com cobre - Coinaski, Djavan Antonio (2019)
Copper (Cu) is a chemical element considered essential for plants, but when in high concentrations it is one of the main heavy polluting metals in the soil. The use of plants associated with microrganisms and organic compounds can promote the reducing of negative effects of the contaminant on them. The objective of this work was to analyze different species of ectomycorrhizal fungi and swine wastewater compost on copper growth and accumulation in Ilex paraguariensis plants grown in copper contaminated soil. To this end, three scientific works were developed, and the first work aimed to determine the influence of the use of ectomycorrhizal fungi on the growth, tolerance and accumulation of copper in Ilex paraguariensis plants grown in copper contaminated soil; the second work was to evaluate the effect of swine wastewater compost (CARS) on copper growth and accumulation in Ilex paraguariensis plants in copper contaminated soil; the third study aimed to determine the influence of the use of ectomycorrhizal fungi associated with the swine wastewater compound on the growth and accumulation of copper in Ilex paraguariensis cultivated in copper contaminated soil. Inoculation of Ilex paraguariensis seedlings wuth ectomycorrhizas UFSC-PT116, UFSC-PT132 and UFSC-SU118 mitigates the phytotoxicity effect caused by excess copper in the soil. The ectomycorrhizal isolate UFSC-PT116 promotes, among the three tested, the highest growth and tolerance of Ilex paraguariensis seedlings grown in copper-contaminated soil. The inoculation of ectomycorrhizas in Ilex paraguariensis promotes less copper accumulation in plants in soils contaminated by this heavy metal. The swine wastewater compost (CARS) added to the soil increases the pseudo-total copper and the copper fraction adsorbed to organic matter. The average proportion of 30% of swine wastewater compost (CARS) in the soil provides a softening effect of copper toxicity in the soil, favoring growth and reducing the accumulation of copper in Ilex paraguariensis plants. The use of ectomycorrhizal fungi and CARS mitigates the negative effect of the 400 mg kg-1 copper dose on the growth of Ilex paraguariensis. Seedlings. Copper content and accumulation in plant tissue of Ilex paraguariensis plants are reduced when associated with the fungus UFSC-PT116 regardless of the addition of CARS in the soil.